Self-consistent molecular mechanism of β2-microglobulin aggregation - Tammara, Vaishnavi; Das, Atanu (Journal of Physical Chemistry B, 2024)
Despite the consensus on the origin of dialysis-related amyloidosis (DRA) being beta(2)-microglobulin (beta(2)m) aggregation, the debate on the underlying mechanism persists because of the continuous emergence of beta(2)m variant- and pH-dependent contradictory results. By characterizing the native monomeric (initiation) and aggregated fibrillar (termination) states of beta(2)m via a combination of two enhanced sampling approaches, we here propose a mechanism that explains the heterogeneous behavior of wild-type (WT) and pathogenic (V27M and D76N) beta(2)m variants in physiological and disease-pertinent acidic pH environments. It appears that the higher retainment of monomeric native folds at neutral pH (native-like) distinguishes pathogenic beta(2)m mutants from the WT (moderate loss). However, at acidic pH, all three variants behave similarly in producing a substantial amount of partially unfolded states (conformational switch, propensity), though with different extents (WT < V27M < D76N). Whereas at the fibrillar end, all beta(2)m variants display a pH-dependent protofilament separation pathway and a higher protofilament binding affinity (stability) at acidic pH, where the relative order of binding affinity (WT < V27M < D76N) remains consistent with pH modulation. Combining these observations, we conclude that beta(2)m variants possibly shift from native-like aggregation to conformational switch-initiated fibrillation as the pH is altered from neutral to acidic. The combined propensity-stability approach based on the initiation and termination points of beta(2)m aggregation not only assists us in deciphering the mechanism but also emphasizes the protagonistic roles of both terminal points in the overall aggregation process.